Strategi Peningkatan Kemampuan Motorik Kasar Kelompok A TK Dwijorini Gentingsari Melalui Seni Tari Kuda Lumping - Kharimah, Kharimah; Arifah, Zaidatul; Rachman, Yenny Aulia (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
The gross motor development of today's children has not met expectations; children still have difficulty imitating the movements taught by teachers. This research aims to determine strategies for improving gross motor skills through the art of lumping horse dance. This type of research is descriptive-qualitative research. The research was conducted at Dwijorini Gentingsari Kindergarten with 14 students. Data collection techniques use observation, interviews, and documentation guidelines. Data is analyzed interactively through data reduction, data presentation, and drawing conclusions. The results of the research show that the gross motor skills of group A children at Dwijorini Gentingsari Kindergarten have not developed well. Supporting factors for learning dance include internal factors within the child, local wisdom, the development of motor skills, encouragement of exploration, and the availability of adequate property. The inhibiting factors for learning dance are children's dancing activities, which are still not very cohesive, dance schedules, which have not been arranged regularly, and some children's lack of confidence in dancing with expression.